Effects of listening to Holy Qur'an recitation and physical training on dialysis efficacy, functional capacity, and psychosocial outcomes in elderly patients undergoing haemodialysis. Issue 1 (1st January 2017) - Frih, Bechir; Mkacher, Wajdi; Bouzguenda, Abir; Jaafar, Hamdi; ALkandari, Salem Ali; Ben Salah, Zohra; Sas, Bart; Hammami, Mohamed; Frih, Ameur
ABSTRACT: The purpose of this study was to determine whether listening to Holy Qur'an recitation would augment the beneficial effects of physical exercise on physiological and psychological measures in elderly patients undergoing haemodialysis. Fifty-three male haemodialysis patients were randomly assigned to an intervention group (listening to Holy Qur'an recitation in combination with endurance–resistance training, n = 28) or a control group (endurance–resistance training only, n = 25). Functional capacity was assessed using the Timed Up and Go test (TUG) and the Six-Minute Walk Test (6MWT). Psychosocial outcomes were assessed using the Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) and Hospital Anxiety and Depression Scale (HADS). Dialysis adequacy ( Kt / V ) was calculated for all patients. After intervention, a significant Group × Period interaction effect was observed for all measured parameters ( p < 0.05), except for 6MWT performance ( p > 0.05). All measured parameters were significantly improved over baseline in both groups, except for Kt / V in the control group ( p > 0.05). Moreover, final measurements were significantly higher in the intervention group than in the control group for all measured parameters, except for 6MWT performance and the physical component summary of the SF-36 ( p > 0.05). In conclusion, the present study showed that listening to a recitation of the Holy Qur'an in combination with interdialytic endurance–resistance training induced an improvement in physical condition and quality of life and a large reduction in anxiety among patients undergoing haemodialysis.